NKG2D-CAR-targeted iPSC-derived MSCs efficiently target solid tumors expressing NKG2D ligand - Shuqing Tang; Yusang Zhang; Peiyun Wang; Qiyu Tang; Yating Liu; Fan Lu; Mengting Han; Miaojin Zhou; Qian Hu; Mai Feng; Desheng Liang (iScience)
Summary: Mesenchymal stem cells (MSCs) hold potential in cancer therapy; however, insufficient tumor homing ability and heterogeneity limit their therapeutic benefits. Obviously, the homogeneous induced pluripotent stem cell (iPSC)-derived mesenchymal stem cells (iMSCs) with enhanced ability of tumor targeting could be the solution. In this study, a CAR containing the NKG2D extracellular domain was targeted at the B2M locus of iPSCs to generate NKG2D-CAR-iPSCs, which were subsequently differentiated into NKG2D-CAR-iMSCs. In vitro, NKG2D-CAR significantly enhanced migration and adhesion of iMSCs to a variety of solid tumor cells expressing NKG2D ligands. RNA sequencing (RNA-seq) revealed significant upregulation of genes related to cell adhesion, migration, and binding in NKG2D-CAR-iMSCs. In A549 xenograft model, NKG2D-CAR-iMSCs demonstrated a 57% improvement in tumor-homing ability compared with iMSCs. In conclusion, our findings demonstrate enhanced targeting specificity of NKG2D-CAR-iMSCs to tumor cells expressing NKG2D ligands in vitro and in vivo, facilitating future investigation of iMSCs as an off-the-shelf living carrier for targeted delivery of anti-tumor agents.